Longing for mania: A case report - (:unkn) unknown (My University, 2021)
INTRODUCTION:Treatment adherence is a frequent problem in bipolar disorder (BD), in some studies, treatment nonadherence frequency is reported as 50%. Side effects of medications and unfavorable personal attitudes toward treatment may also have a negative impact on treatment adherence. Here, we present a bipolar patient who had numerous hospitalization as a result of treatment nonadherence. CASE PRESENTATION:Mr. B. is a 37 year-old patient, has graduated from university, and working as an academician. Three years ago, he was brought to our clinic by his family with symptoms of expansive mood, decreased need for sleep, increased activity, persecutory delusions. The patient who had no insight was hospitalized and detailed evaluation showed his psychiatric history began at age 23 with manic episode and although he has used various oral medication, he had one depressive and up to ten manic episodes with repetitive hospitalizations almost every year. Due to he had frequent episodes as a consequence of poor medication adherence, it was decided to switch a LAI form paliperidone palmitate 100mg/month with oral olanzapine, in addition to lithium. Since he did not have volunteer to use medications, detailed questioning showed the patient longed for manic episodes that felt him strong and intelligent, also he was afraid of the drugs would make his attention worse. He was informed about the concequences of poor treatment adherence which may worsen the course of BD and so indirectly worsen cognitive performance thus he has convinced to use LAI. Following three years, neither depressive nor manic episode has not been observed under treatment. Moreover, there has been improvement in his social and occupational functioning. CONCLUSIONS: Noncompliance with maintenance treatment in BD is associated with greater rates of disease relapse and re-hospitalization. Clinicians must inform the patients about the concequences of poor treatment adherence which may worsen the course of BD.
Keywords: treatment adherence; bipolar disorder; long acting injection